Stories of Survival : Arkansas Farmers during the Great Depression - Downs, William David, 1932- (Book collections on Project MUSE., 2015)
Through dozens of in-depth interviews representing all sections of the state, farm families recall their best times, their worst times, and day-to-day experiences such as chores, washing, bathing, clothes making, medical care, home remedies, spiritual life, courtship and marriage, and school experiences. Their stories reveal how ordinary men and women, frequently living in abject poverty, endured cataclysmic natural disasters and economic collapse with extraordinary courage, faith, resourcefulness, and a good sense of humor.